BIOSORPTION STUDY OF Cu (II) FOR GRANULES CALCIUM ALGINATE BIOPOLYMER - Tapia H., Nelson (2003)
Were obtained dried calcium alginate beads of 1 mm diameter. The optimum pH for the biosorption of Cu (II) is between 4.5 and 5. The study of the kinetics of biosorption was determined that the thermodynamic equilibrium is reached after 24 h. The data fit very well with the Langmuir model, and shows that the maximum biosorption is Qmax = 80.6 mg / g.